The Ability of the Fourth Semester Students in Identifying the Adjectives and Adjectival Phrases from English Translation of Surah Al-Mulk - Djamdjuri, Dewi Suriyani (ENGLISH JOURNAL, 2016)
It is well known that the Holy Book contains so much knowledge that useful for human life in this world until Hereafter. The knowledge that urges human to learn, study, explore and think deeply to comprehend and understand, so that the knowledge can be applicable in human life. The research that the writer did is about the structure of the language used. As the noble Qur’an has been translated so carefully, it seems interesting to learn its structure, for one of the basic elements in ELT structure is important to master. In addition, the students will be able to comprehend the teaching in surah Al-Mulk whenever they analyze it. However the students mostly feel difficult to understand the structure, but the more they interact with the Qur’an the more they will understand. The writer focuses the research on the ability of the students in analyzing surah Al-Mulk by identifying the adjectives and the sequences of adjectival phrases. The students were demanded to notice the adjective then the sequence of adjectival phrases in surah Al-Mulk. The writer did the research under the title: “The Ability of the Fourth Semester Students in Analyzing the English Translation of Surah Al Mulk by Identifying the Adjectives and the Sequences of Adjectival Phrases”. Some students succeed in analyzing surah Al Mulk but some students still made mistakes by identifying adjectival phrase incorrectly